Comparison of the Antimony Cementation from Chloride Media Using Various Cementators - ÇETİNER, BURCU NİLGÜN; AKTAŞ, SERDAR (My University, 2022)
This study compares the cementation performance of metallic iron, metallic aluminum, and metallic tin in terms of the reaction conditions and parameters in synthetic antimony chloride solutions. The effects on the antimony recovery (%) caused by the cementators\" types, stirring speed, reaction time, and temperatures were explored thoroughly. The cementation kinetics of antimony were also explored for each cementator. The activation energies were determined to be 10.99, 9.09, and 13.58 kJ mol(-1) for Al, Fe, and Sn, respectively. The results reveal that the reaction is diffusion controlled, and comparable results were obtained for each cementator. At 25 degrees C, 40 mg of iron powder was found to reduce all antimony ions (i.e., approx. 99% recovery), but even when 100 mg of Al and Sn cementators were used, the antimony recovery did not reach 100%. This result shows that iron is the best candidate to cement antimony out of the solution.
Keywords: Maden Mühendisliği ve Teknolojisi; Metalurji ve Malzeme Mühendisliği; Mühendislik ve Teknoloji; Mining Engineering and Technology; Metallurgical and Materials Engineering; Engineering and Technology; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MADENCİLİK VE MİNERAL İŞLEME; Mühendislik; METALLURGY & METALLURGICAL ENGINEERING; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); MINING & MINERAL PROCESSING; ENGINEERING; General Engineering; General Materials Science; Engineering (miscellaneous); Physical Sciences; Cementation; Reduction; Replacement; Antimony; Chloride media; WASTE-WATER; COPPER; RECOVERY; GOLD; ENVIRONMENT; ZINC; KINETICS; MOBILITY; REMOVAL; SOILS; Cementation; Reduction; Replacement; Antimony; Chloride media